A global survey of alternative splicing in allopolyploid cotton: landscape, complexity and regulation. Issue 1 (11th September 2017) - Wang, Maojun; Wang, Pengcheng; Liang, Fan; Ye, Zhengxiu; Li, Jianying; Shen, Chao; Pei, Liuling; Wang, Feng; Hu, Jiang; Tu, Lili; Lindsey, Keith; He, Daohua; et al.
Summary: Alternative splicing (AS) is a crucial regulatory mechanism in eukaryotes, which acts by greatly increasing transcriptome diversity. The extent and complexity of AS has been revealed in model plants using high‐throughput next‐generation sequencing. However, this technique is less effective in accurately identifying transcript isoforms in polyploid species because of the high sequence similarity between coexisting subgenomes. Here we characterize AS in the polyploid species cotton. Using Pacific Biosciences single‐molecule long‐read isoform sequencing (Iso‐Seq), we developed an integrated pipeline for Iso‐Seq transcriptome data analysis (https://github.com/Nextomics/pipeline-for-isoseq ). We identified 176 849 full‐length transcript isoforms from 44 968 gene models and updated gene annotation. These data led us to identify 15 102 fibre‐specific AS events and estimate that c . 51.4% of homoeologous genes produce divergent isoforms in each subgenome. We reveal that AS allows differential regulation of the same gene by miRNAs at the isoform level. We also show that nucleosome occupancy and DNA methylation play a role in defining exons at the chromatin level. This study provides new insights into the complexity and regulation of AS, and will enhance our understanding of AS in polyploid species. Our methodology for Iso‐Seq data analysis will be a useful reference for the study of AS in other species.